Politics in the Gutters : American Politicians and Elections in Comic Book Media - Knopf, Christina M., 1980- (Book collections on Project MUSE., 2021)
"From the moment Captain America punched Hitler in the jaw, comic books have always been political, and whether it is Marvel's chairman Ike Perlmutter making a campaign contribution to Donald Trump in 2016 or Marvel's character Howard the Duck running for president during America's bicentennial in 1976, the politics of comics have overlapped with the politics of campaigns and governance. Pop culture opens avenues for people to declare their participation in a collective project and helps them to shape their understandings of civic responsibility, leadership, communal history, and present concerns. Politics in the Gutters: American Politicians and Elections in Comic Book Media opens with an examination of campaign comic books used by the likes of Herbert Hoover and Harry S. Truman, follows the rise of political counterculture comix of the 1960s, and continues on to the graphic novel version of the 9/11 Report and the cottage industry of Sarah Palin comics. It ends with a consideration of comparisons to Donald Trump as a supervillain and a look at comics connections to the pandemic and protests that marked the 2020 election year. More than just escapist entertainment, comics offer a popular yet complicated vision of the American political tableau. Politics in the Gutters considers the political myths, moments, and mimeses, in comic books-from nonfiction to science fiction, superhero to supernatural, serious to satirical, golden age to present day-to consider how they represent, re-present, underpin, and/or undermine ideas and ideals about American electoral politics"--